Continuity of care experienced by patients in a multi-institutional pancreatic care network: a pilot study - J. S. Hopstaken; D. van Dalen; B. M. van der Kolk; E. J. M. van Geenen; J. J. Hermans; E.C. Gootjes; H. J. Schers; A. M. van Dulmen; C. J. H. M. van Laarhoven; M. W. J. Stommel (BMC, 2021)
Abstract Background Over the past decades, health care services for pancreatic surgery were reorganized. Volume norms were applied with the result that only a limited number of expert centers perform pancreatic surgery. As a result of this centralization of pancreatic surgery, the patient journey of patients with pancreatic tumors has become multi-institutional. To illustrate, patients are referred to a center of expertise for pancreatic surgery whereas other parts of pancreatic care, such as chemotherapy, take place in local hospitals. This fragmentation of health care services could affect continuity of care (COC). The aim of this study was to assess COC perceived by patients in a pancreatic care network and investigate correlations with patient-and care-related characteristics. Methods This is a pilot study in which patients with (pre) malignant pancreatic tumors discussed in a multidisciplinary tumor board in a Dutch tertiary hospital were asked to participate. Patients were asked to fill out the Nijmegen Continuity of Care-questionnaire (NCQ) (5-point Likert scale). Additionally, their patient-and care-related data were retrieved from medical records. Correlations of NCQ score and patient-and care-related characteristics were calculated with Spearman's correlation coefficient. Results In total, 44 patients were included (92% response rate). Pancreatic cancer was the predominant diagnosis (32%). Forty percent received a repetition of diagnostic investigations in the tertiary hospital. Mean scores for personal continuity were 3.55 ± 0.74 for GP, 3.29 ± 0.91 for the specialist and 3.43 ± 0.65 for collaboration between GPs and specialists. Overall COC was scored with a mean 3.38 ± 0.72. No significant correlations were observed between NCQ score and certain patient-or care-related characteristics. Conclusion Continuity of care perceived by patients with pancreatic tumors was scored as moderate. This outcome supports the need to improve continuity of care within multi-institutional pancreatic care networks.